Children with cerebral palsy and drooling – their clinical profile and management. (4th April 2011) - Rekha, M S; Gladstone, M; Hanumanthiah, H; Giri, P; Bassi, Z
Abstract : Aim: Sialorrhoea causes significant social handicap and impairment in quality of life for children with cerebral palsy (CP). A review was conducted in a tertiary centre to ascertain the prevalence of drooling in children with CP and understand the spectrum of disease in these patients by comparison with those in whom drooling was not recorded as a major problem. Method: Retrospective data collection from case records of children with CP attending the unit. Results: In our cohort of 126 children, 16.8% (n=20, median age 11, males – 12) had drooling, 83% (n=99, median age 10, males – 62) did not have drooling (data was incomplete in 7). We noted the clinical profile of children who had drooling and compared it with those who did not drool. Data was incomplete in some, but overall we noted the following in drooling versus non drooling groups, GMFCS (Gross Motor Functional Classification System – IV and V) 60% versus 26%; Learning difficulties 88% versus 67%; Communication difficulties 84% versus 45%; Gastrostomy feeding in 40% versus 3%; Anti-spasticity medication use (Baclofen) 10% versus 18%; Seizures 63% versus 27%. In children with drooling, spastic quadriplegia was the most common type of CP (45%, n=9). 63% were in special school. 46.6% had gastro-oesophageal reflux, all of whom were on anti-reflux medication. Medical management included hyoscine patch in 63% and oral medication in 33%. 1 child had intra glandular Botox and one needed salivary gland surgery. Conclusions: In our cohort, children with drooling presented across the spectrum of motor ability, 60% (GMFCS IV-V) and 40% (GMFCS of I to III). Hence GMFCS on its own was not a good predictor for drooling in our cohort. However, children with drooling were more likely to have difficulties with oromotor skills requiring assisted feeding, gastro-oesophageal reflux, seizures and communication. Interestingly, Baclofen was not a major contributor to drooling in our cohort. In view of our findings we have developed a drooling pathway and a one-stop drooling clinic to provide multi-disciplinary assessment and management.